2021
DOI: 10.1039/d1ta01464a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-length scale 5D diffraction imaging of Ni–Pd/CeO2–ZrO2/Al2O3 catalyst during partial oxidation of methane

Abstract: Operando 5D X-ray diffraction imaging reveals complex heterogeneities across multiple length scales in a catalytic reactor for the partial oxidation of methane reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 98 publications
0
20
0
Order By: Relevance
“…Hence, the small sample sizes of CMRs (typically <1.5 mm diameters) restrict concentration and temperature measurements to the reactor inlet and outlet, while there is no access to the dynamic and transient chemistry occurring within the catalyst bed. Larger reactor diameters limit the applicability of absorption techniques, whereas X-ray diffraction (XRD) or tomographic techniques using high energies can feasibly be applied on larger reactor diameters, as shown in several studies (O'Brien et al, 2009;Wragg et al, 2012;Vamvakeros et al, 2018;Vamvakeros et al, 2020;Matras et al, 2021). However, these studies, as is the case for most spatially resolved synchrotron operando studies, measure only the catalyst in a spatially resolved manner.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the small sample sizes of CMRs (typically <1.5 mm diameters) restrict concentration and temperature measurements to the reactor inlet and outlet, while there is no access to the dynamic and transient chemistry occurring within the catalyst bed. Larger reactor diameters limit the applicability of absorption techniques, whereas X-ray diffraction (XRD) or tomographic techniques using high energies can feasibly be applied on larger reactor diameters, as shown in several studies (O'Brien et al, 2009;Wragg et al, 2012;Vamvakeros et al, 2018;Vamvakeros et al, 2020;Matras et al, 2021). However, these studies, as is the case for most spatially resolved synchrotron operando studies, measure only the catalyst in a spatially resolved manner.…”
Section: Introductionmentioning
confidence: 99%
“…temperature, pressure, potential, chemical environment). [20][21][22][23][24][25][26] The quantity and speed of this data acquisition poses challenges to traditional image reconstruction and analysis techniques. The limits to what is currently achievable with chemical imaging techniques is currently oen determined by the density of sampling required for the sinogram in order to achieve good quality image reconstructions.…”
Section: Introductionmentioning
confidence: 99%
“…A series of noble-metal-supported catalysts have been reported in the catalytic oxidation of ethyl acetate, such as Ru/SnO 2 , Ag/LaCoO 3 , Ag/CeO 2 , Au/CeO 2 , Pd/Cr 2 O 3 -ZrO 2 , and Pd/Al 2 O 3 , and the performance of noble-metal-supported catalysts is significantly improved compared with that of certain supports because the strong metal–support interactions (SMSIs) enhance the surface oxygen vacancies, surface reactive oxygen species, and low-temperature redox ability. Among these noble metals, Pd has more abundant reserves and lower cost than other noble metals and can have a strong interaction with supports, showing high catalytic activity, so it is a critical material for the catalysis of VOCs. As a stable, richly abundant, and cheap rare earth material, CeO 2 has become a hotspot of support material because of its excellent oxygen storage and release capacity, conversion capacity between valence states, and abundant oxygen vacancy, thus providing surface and pore structure for noble metal dispersions. Moreover, CeO 2 has morphological diversity, and studies have shown that the morphology of CeO 2 has a significant impact on catalytic activity. For example, Feng et al prepared three kinds of CeO 2 with different morphologies and found that the concentration of surface oxygen vacancies was affected by the morphology, which led to the difference in catalytic activity. At present, it has been found that the SMSIs on the interface of noble-metal-supported catalysts would significantly influence the activity and stability of the catalysts, , while the effect of support morphology on SMSI needs further research.…”
Section: Introductionmentioning
confidence: 99%